Correlation between No-slip and Slip Boundary Conditions Associated with a Two-dimensional Navier-Stokes Flows in a Plane Diffuser - Ibragimov, Ranis; Vatchev, Vesselin (Journal of Vibration Testing and System Dynamics, 2026)
We examine the viscous effects of slip boundary conditions for the model describing two-dimensional Navier-Stokes flows in a plane diffuser. It is shown that the velocity profile is related to a half period shifted Weierstrass function with two parameters. This allows to approximate the explicit solution by a Taylor series expansion with two new micro-parameters, that can be measured in physical experiments. It is shown that the assumption for no-slip boundary conditions is stable in the sense that a small perturbation of the boundary values result in a small perturbation in the solutions.